Broadband planar 90 degrees loaded-stub phase shifter - S. El Marini; R. Mandry; J. Zbitou; A. Errkik; A. Tajmouati; M. Latrach (Universitas Ahmad Dahlan, 2020)
The differential phase shifter is an interesting four-port passive microwave network composed of two separate lines, the main line and the reference line, and providing stable phase difference between the two output signals over the specified bandwidth of interest. The most common differential phase shifter is the coupled-line Schiffman phase shifter. In this paper, a novel 90 degrees differential microstrip phase shifter configuration employing a half wavelength transmission line loaded with three open stubs is presented, the proposed design could achieve excellent performance with low phase variation over a wide bandwidth compared to the standard Schiffman phase shifter. The simulated results accomplished with the use of CST Microwave Studio and advanced design system (ADS), were found to be in good agreement and have shown that the proposed loaded-stub phase shifter achieved less than 1.1 dB insertion loss, greater than 13 dB return loss and constant 90±5 degrees phase shift over an 89 percent bandwidth.